Export market exit, financial pressure and the crisis - Holger Görg; Marina-Eliza Spaliara (Kiel Institute for the World Economy (IfW), 2013)
Using firm-level data for the UK, we investigate the link between firms' financial health, borrowing ratio and export exit, paying special attention to the recent financial crisis. Our results show that deterioration in the financial position of firms has increased the hazard of export exit during the crisis. We also find that the sensitivity of export exit to changes in firms' financial condition is higher during the crisis for those firms which face increases in loan spreads associated with the firm-specific interest rate.
Keywords: F1; L2; G3; 330; financial pressure; firm exit; financial health; exports